KAJIAN EKSTRAKSI DAN MODIFIKASI PATI DARI KARABENGUK (Mucuna pruriens L.) - Candy Emerald Arvisdea, - (2021)
Mucuna pruriens is a plant that is rarely used but has the potential to be a new source of starch. This is related to the physicochemical and functional properties of starch from Mucuna pruriens. However, native starch from Mucuna pruriens has several limitations, so starch modification was carried out. This study aimed to study several methods of extracting and modifying starch, physicochemical characteristics (moisture, protein, lipid, ash, fiber, size and morphology) and functional properties (swelling, solubility, gelatinization and paste) of Mucuna pruriens starch. This study is a literature review with a narrative model that examines two extraction methods and three modifications of Mucuna pruriens starch from four Scopus indexed articles Q1 and Q2 published in 2002-2015. The results showed that starch extraction and modification can be carried out with or without a catalyst and neutralizing solution and is generally carried out at a drying temperature of 30-60C for 12-48 hours. The physicochemical characteristics of native Mucuna pruriens starch have moisture content of 9.2-9.82%, protein 0.71-1.9%, lipid 0.4-2%, fiber 7%, and ash 0.28-5%, and starch granule size ranges from 12-45 m with oval morphology. Meanwhile, the physicochemical characteristics of modified Mucuna pruriens starch have moisture content of 9.7-11.5%, protein 0-1.2%, lipid 0.57-1%, fiber 1-3.4%, and ash 1-0. ,58%, and the size of starch granules ranged from 12-31 m with oval morphology. The functional characteristics of native Mucuna pruriens starch consisted of swelling 13.3-16.6 g/g, solubility 14.3-16.2%, gelatinization enthalpy 10.52 J/g, and peak viscosity of starch in the range of 256-320 BU. Meanwhile, the functional characteristics of modified Mucuna pruriens starch have swelling 6.7-15.6 g/g, solubility 7.7-53.6%, enthalpy of gelatinization 4.10-10.32 J/g, and peak viscosity of starch at range 120-410 BU. Based on these starch properties, Mucuna pruriens has potential as a new alternative source of starch. Keyword: starch, Mucuna pruriens, extraction, modification, physicochemical